Early Results of Physician Modified Fenestrated Stent Grafts for the Treatment of Thoraco-abdominal Aortic Aneurysms. Issue 5 (November 2015) - Cochennec, F.; Kobeiter, H.; Gohel, M.; Leopardi, M.; Raux, M.; Majewski, M.; Desgranges, P.; Allaire, E.; Becquemin, J.P.
Abstract : Objectives: The aim was to determine whether physician modified stent grafts (PMSGs) are safe and effective for the treatment of high risk patients with thoraco-abdominal aortic aneurysms (TAAAs). Design: This was a retrospective single institution study. Material: Consecutive patients with TAAA undergoing endovascular repair using a PMSG between January 2012 and June 2014 were evaluated. Methods: Fenestrations to preserve branch vessels were created in TX2 thoracic (Cook Medical) stent grafts. Pre- intra- and post-operative data were recorded by means of a prospectively maintained database. Results: Eleven high risk patients with TAAA (type I, n  = 4; type III, n  = 3; type IV, n  = 3; type V, n  = 1) underwent fenestrated endovascular repair using PMSGs. Indications were painful aneurysm ( n  = 5), >70 mm rapidly enlarging aneurysm ( n  = 4), saccular aneurysm ( n  = 1), and visceral patch false aneurysm after open repair of a type IV TAAA ( n  = 1). In four asymptomatic patients, an additional fenestration was created for temporary selective sac perfusion and occluded 2–4 weeks later. Median duration for stent graft modifications was 2 hours (range 1–3 hours). The median number of fenestrations was three (range 2–4). One patient died during the post-operative period from colonic ischemia, giving a 9% in hospital mortality rate. Four (36%) patients presented with moderate to severe complications. One (9%) patient presented with a paraparesis that resolved completely after spinal fluid drainage. Among surviving patients, four required early endovascular re-intervention for type III endoleak ( n  = 2), type Ia endoleak ( n  = 1), or target vessel cannulation failure ( n  = 1). The median follow up time was 6 months (range 3–20 months). During follow up, no other complications occurred and all target vessels remained patent. One patient presented with a persistent type II endoleak. Conclusion: PMSGs provided acceptable short-term results and may be a management option for the treatment of TAAA in selected high risk patients. Durability concerns need to be assessed in additional studies with long-term follow up.